Analisis Nilai Toleransi Novel 99 Cahaya di Langit Eropa dan Relevansinya dalam Pembelajaran Bahasa Indonesia - Ramadhanty, Widya Risky; Putri, Nur Aini Saura (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The value of tolerance is part of the norms that exist in society in terms of religion, culture, language and nation. An attitude of tolerance is very much needed in social life as a unifier of differences because the existence of differences will give rise to diversity in a person's results, thoughts and insights. The research method in this study is descriptive qualitative with the data source being the novel 99 Cahaya di Langit Europa. Collecting data by (1) Reading the novel 99 Cahaya di Langit Europe by paying close attention to each meaning conveyed by the author. (2) Looking for text quotes that match the value of tolerance. (3) Analyzing the data results by identifying parts relating to inter-ethnic tolerance contained in the novel 99 Cahaya di Langit Europa. (4) Analyzing the relevance of the value of tolerance contained in the novel 99 Cahaya di Langit The sky of Europe by learning Indonesian in high school. (5) Summarize the results of the analysis of the novel. The results of the analysis show that the values ​​of tolerance contained in the novel 99 Cahaya di Langit Europa are intercultural tolerance, language tolerance and religious tolerance. Then this novel is relevant to class XII Indonesian language learning at KD 3. menganalisis isi dan kebahasaan novel.